Improved quality-of-life of caregivers of children with asthma through guideline-based management. (9th August 2017) - Sheikh, Shahid I.; Pitts, Judy; Ryan-Wenger, Nancy A.; Kotha, Kavitha; McCoy, Karen S.; Stukus, David R.
ABSTRACT: Objective: The quality of life (QOL) of caregivers of children with asthma may be related to children's responses to asthma management. Aim: To evaluate change in QOL over time of caregivers of children with asthma through guideline-based management. Design: This was a 3-year prospective cohort study of children with asthma referred to our pediatric asthma center. Families completed Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ), the Asthma Control Test™ (ACT), and reported the number of days/month of albuterol use and wheezing at each clinic visit. Results: We enrolled 143 children, ages 7–17 years (mean = 10.6 ± 2.9), 56.6% male, 70.6% Caucasian. Patients were managed by the same MD ( n = 65, 45.5%) or APN ( n = 78, 54.5%) over time. The mean total PACQLQ significantly increased over the 3-year period ( F = 67.418, p < .001). Total scores at the first visit were 4.8 ± 1.6, which improved to 6.1 ± 1 at the 3-month follow-up visit. This improvement was sustained at the 1, 2, and 3-year clinic visits. PACQLQ emotional function ( F = 60.798, p < .001) and activity limitation ( F = 41.517, p < .001) domains significantly improved as well. PACQLQ scores were significantly associated with improved ACT scores ( r = .37 to .47, p < .05), fewer days/month of albuterol use ( r = −.25 to −.36., p < .05), and wheezing ( r = −.28 to −.33, p < .05). There were no significant differences in PACQLQ, or asthma clinical outcome measures between MD and APN providers. Conclusion: Use of National Asthma Education and Prevention Program (NAEPP) guidelines significantly improved QOL of caregivers of children with asthma and in asthma-related symptoms. Improvements over time were independent of type of providers.